A proposal for scientific analysis on the signboard color of gwanghwamoon - Joo, Jongwoo; Lee, Yonghwan (International Journal of Engineering and Technology, 2018)
Background/Objectives: The analysis plan on the signboard of Gwanghwamoon is the research inferencing the background color and the handwriting color of the signboard by scientifically analyzing the gelatin glass plate image of Gwanghwamoon (1916) possessed by National Museum of Korea, the gelatin glass plate image of Gwanghwamoon (1902) possessed by The University of Tokyo, Japan, and the printed image of Gwanghwamoon (around 1893) possessed by Smithsonian Museum, USA.Methods/Statistical analysis: This study aimed to reproduce the then photographing condition and equipment of the old pictures in order to compare and analyze the three old pictures aforementioned.Findings: The restoration of tangible cultural properties through picture analysis and reproduction research will lay a cornerstone and the excellent case for future restoration project of similar tangible cultural properties. In restoration of cultural properties, scientific historical research is critical and basic process. Moreover, in case that photograph data exists, it can be utilized as a very valuable evidence data.Improvements/Applications: On the other hand, the photograph data can also be a dangerous trap without scientific research analysis that reproduces the condition of the time of the shooting; hence, the results of this study can be a good example of scientific analysis in restoration work.Â Â